ANALISIS EFEKTIVITAS PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) KAMPUNG HORTIKULTURA BINAAN PT. PUPUK SRIWIDJAJA PALEMBANG - Lestari lestari (Jurnal AGRIBIS, 2021)
This study aims to (1) Determine the impact of the Horticulture village's CSR program under the guidance of PT. Sriwidjaja Palembang Fertilizer. (2) Knowing the       effectiveness of the CSR program in the Horticulture village fostered by PT. Sriwidjaja Palembang Fertilizer. This research has been carried out at Posdaya Kebumen Gemilang Sejahtera Kelurahan 2 Ilir, Ilir Timur District 2 Palembang in January to February 2020.  The method used in this study is a simple random method. Samples were taken as many as 25 people from 114 female members of the Posdaya Gemilang Sejahtera farmer group. Data collected in this study are primary and secondary data. Data processing methods used are descriptive analysis and Microsoft Excel data processing.  The results showed that (1) the CSR program in the Horticulture village was implemented through the distribution of aid accompanied by guidance and counseling from the field of Partnership and Community Development Program (PKBL) of PT. Sriwidjaja Palembang Fertilizer. (2) The fostered Horticulture village program as a whole is included in the very effective criteria with a score of 35.96 or 79.91% of the ideal value with the criteria of each indicator, namely: very effective participation indicators, indicators of effective time suitability, indicators of program benefits are very effective, indicators of program sustainability are very effective, and indicators of increasing insight are very effective.Key words: Corporate Social Responsibility, Effectiveness, Village fostered